Ask Question
6 February, 04:34

If f (x) = 16x - 30 and g (x) = 14x - 6, for which value of x does (f-g) (x) = 0?

-18

0 - 12

0 12

0 18

+3
Answers (2)
  1. 6 February, 05:41
    0
    f (x) = 16x - 30 (Given)

    g (x) = 14x - 6 (Given)

    Find (f - g) (x):

    (f - g) (x) = f (x) - g (x)

    (f - g) (x) = (16x - 30) - (14x - 6)

    (f - g) (x) = 16x - 30 - 14x + 6

    (f - g) (x) = 2x - 24

    Solve x:

    Given that (f - g) (x) = 0

    2x - 24 = 0

    2x = 24

    x = 12

    Answer: x = 12
  2. 6 February, 06:16
    0
    x = 12

    Step-by-step explanation:

    note that f - g) (x) = f (x) - g (x), hence

    16x - 30 - (14x - 6) = 0

    16x - 30 - 14x + 6 = 0

    2x - 24 = 0 (add 24 to both sides)

    2x = 24 (divide both sides by 2)

    x = 12
Know the Answer?